2007
DOI: 10.1111/j.1528-1167.2006.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Outcome after Resection of Supratentorial Cavernous Malformations: A Study of 168 Patients

Abstract: Summary: Purpose:The optimal management of cerebral cavernous malformations (CCMs) with epileptic seizures is still a matter of debate. The aim of our study was to examine seizure outcome in the largest published series of surgically treated patients with epilepsy due to a supratentorial CCM, and to define predictors for good surgical outcome.Methods: We retrospectively studied 168 consecutive patients with a single supratentorial CCM and symptomatic epilepsy in a multicenter study. Pre-and postoperative clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
144
6
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 16 publications
5
144
6
1
Order By: Relevance
“…However, in lesional epilepsy and especially after CM resection in patients with epilepsy, outcomes are generally reported to be favorable, with rates of Engel Class I outcomes of 65%-86% in the literature. 4,9,15,21,29,64,80,84,87,88 Nevertheless, the CM seizure outcome results in the current study are among the top results reported in the literature. The rationale of these optimal results could be that we also performed resection of the hemosiderotic rim in nearly all patients with CM within the underlying study, as reported earlier.…”
Section: Seizure Outcomes From Different Pathological Entitiesmentioning
confidence: 60%
“…However, in lesional epilepsy and especially after CM resection in patients with epilepsy, outcomes are generally reported to be favorable, with rates of Engel Class I outcomes of 65%-86% in the literature. 4,9,15,21,29,64,80,84,87,88 Nevertheless, the CM seizure outcome results in the current study are among the top results reported in the literature. The rationale of these optimal results could be that we also performed resection of the hemosiderotic rim in nearly all patients with CM within the underlying study, as reported earlier.…”
Section: Seizure Outcomes From Different Pathological Entitiesmentioning
confidence: 60%
“…Surgery has particularly proven to be an effective treatment in CCMs manifesting with epilepsy. Patients become seizure-free in about 70% to 80% [1,3]. In our patients, 11 of 14 (78%) became seizure-free.…”
Section: Surgical Outcomementioning
confidence: 93%
“…There is a large variety of studies reporting excellent surgical outcome following removal of CCMs [1,3,7,21]. Thus, in a large series of 72 patients, there was no mortality, and the immediate perioperative morbidity rate was 29.2% (21/72), while the rate of long-term morbidity was 5.5% (4/72).…”
Section: Surgical Outcomementioning
confidence: 93%
“…Baumann et al 31 recently published a large non-randomized study on seizure outcome after resection of single supratentorial CMs. Predictors for favorable seizure outcome after removal of CM include age >30 years, lesion size <1.5 cm, no additional seizure focus on eeG, and presence of simple partial or complex seizures.…”
Section: Managementmentioning
confidence: 99%